2007
DOI: 10.1007/s10393-007-0093-5
|View full text |Cite
|
Sign up to set email alerts
|

Spread of Chytridiomycosis Has Caused the Rapid Global Decline and Extinction of Frogs

Abstract: The global emergence and spread of the pathogenic, virulent, and highly transmissible fungus Batrachochytrium dendrobatidis, resulting in the disease chytridiomycosis, has caused the decline or extinction of up to about 200 species of frogs. Key postulates for this theory have been completely or partially fulfilled. In the absence of supportive evidence for alternative theories despite decades of research, it is important for the scientific community and conservation agencies to recognize and manage the threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
955
2
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,045 publications
(974 citation statements)
references
References 42 publications
11
955
2
6
Order By: Relevance
“…We review our findings with reference to the specifics of our study system, highlighting where our approach offers insight that is broadly relevant to endangered species and protected area management, including IUCN Red List assessments and the treatment of data-deficient species. The effects of Bd on amphibians are inherently nonrandom with respect to the species affected [13,42], and the role of Bd in many of the 32 declining stream or moist bog/soak species in the high-Bd group (node 4) in this study has been reasonably well documented (e.g. Pseudophryne corroborree, Taudactylus acutirostris, Taudactylus eungellensis, Litoria (Nyctimistes) dayi, Litoria genimaculata, Litoria leseuerii, Litoria pearsoniana, Litoria rheocola; [13,18,43]).…”
Section: Discussion (A) a Global Perspectivementioning
confidence: 57%
See 1 more Smart Citation
“…We review our findings with reference to the specifics of our study system, highlighting where our approach offers insight that is broadly relevant to endangered species and protected area management, including IUCN Red List assessments and the treatment of data-deficient species. The effects of Bd on amphibians are inherently nonrandom with respect to the species affected [13,42], and the role of Bd in many of the 32 declining stream or moist bog/soak species in the high-Bd group (node 4) in this study has been reasonably well documented (e.g. Pseudophryne corroborree, Taudactylus acutirostris, Taudactylus eungellensis, Litoria (Nyctimistes) dayi, Litoria genimaculata, Litoria leseuerii, Litoria pearsoniana, Litoria rheocola; [13,18,43]).…”
Section: Discussion (A) a Global Perspectivementioning
confidence: 57%
“…A third category grouped species declining owing to 'enigmatic' (unknown) causes [10]. With the discovery of chytridiomycosis [18,19], many of these enigmatic declines have been attributed to the effects of this pandemic disease [13]. Nevertheless, in contrast to the progress that has been made in addressing habitat degradation in recent quantitative studies of extinction risk in amphibians (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be seen if the speed of evolution will be rapid enough to prevent extinctions of the most heavily impacted species [2,6,8,38,41,42]. Management actions to conserve these species face the challenge of reducing disease impacts to prevent extinction without compromising species' evolutionary response to this and other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Chytridiomycosis is a recently discovered, globally important, emerging amphibian disease that is caused by the fungal pathogen Batrachochytrium dendrobatidis (Bd). In some parts of the world this pathogen has caused mass die-offs and even extinctions (Lips et al 2005;Skerratt et al 2007), whereas in others amphibians are heavily infected but show no acute signs of disease (Rothermel et al 2008;Kinney et al 2011). Amphibians in eastern North America fall into the latter category, where infection prevalence may be high (Longcore et al 2007;Rothermel et al 2008;Gaertner et al 2009;Kinney et al 2011;Chatfield et al 2012) yet mass die-offs attributable to chytridiomycosis have not been observed.…”
Section: Introductionmentioning
confidence: 99%